2018
DOI: 10.1002/mc.22931
|View full text |Cite
|
Sign up to set email alerts
|

Cytoglobin ameliorates the stemness of hepatocellular carcinoma via coupling oxidative‐nitrosative stress signals

Abstract: Cancer stem cells (CSCs) account for tumor self‐renewal and heterogeneity. Oxidative‐nitrosative stress (ONS) is an independent etiologic factor throughout tumorigenesis. Emerging evidences indicated that the interaction of ONS with CSCs contributes to tumor progression and resistance to chemoradiotherapy. Cytoglobin (Cygb) is a member of human hexacoordinate hemoglobin family and acts as a dynamic mediator of redox homeostasis. We observed that Cygb is significantly deregulated in human hepatocellular carcino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…A recent study found that Cygb was deregulated in HCC tissue and the decrease aggravated the growth of LCSCs. Furthermore, Cygb absence promoted LCSC phenotypes and PI3K/Akt activation in HCC progression but inhibited HCC proliferation and LCSC stemness in an ONSdependent manner (Zhang et al, 2019).…”
Section: Cygbmentioning
confidence: 98%
“…A recent study found that Cygb was deregulated in HCC tissue and the decrease aggravated the growth of LCSCs. Furthermore, Cygb absence promoted LCSC phenotypes and PI3K/Akt activation in HCC progression but inhibited HCC proliferation and LCSC stemness in an ONSdependent manner (Zhang et al, 2019).…”
Section: Cygbmentioning
confidence: 98%
“…The analysis of IHC data was performed as previously described with some modification in ref. (Zhang et al 2019). The total score is equal to the staining intensity multiplied by the percentage of positive cells or field, ≤ 3 is considered as negative expression, > 3 is considered as positive expression.…”
Section: Immunohistochemistry Analysismentioning
confidence: 99%